The importance of the non-financial determinants of the lease versus buy decision for corporate office real estate in Johannesburg - Chetty, Jeremy John (My University, 2017)
The objective of this study is to provide empirical support to the study of corporate real estate by classifying and providing proof on the significance of the non-financial determinants of the lease versus buy decision for office real estate in Johannesburg. By means of a logistic regression coupled to the use of a Kruskal-Wallis test, this study sought insight to company characteristics, locational and physical attributes of office real estate that could predict the lease versus buy decision for corporate real estate based on a survey involving 13 companies occupying office real estate located in Johannesburg. The results do not show a positive correlation between company and site specific characteristics. These were not significant predictors of the lease versus buy decision for corporate real estate. The results indicate that the majority of the respondents prefer a combination of leasing and owning versus solely leasing or owning their corporate real estate. The dataset used in this study is based on a survey that was conducted online, which involved 13 companies occupying corporate office real estate. The small sample size affected the confidence level of predicting the outcome of the decision. This paper demonstrates the need for a broader theoretical system to comprehensively investigate the lease versus buy decision for corporate real estate, which is often limited to financial aspects, but should also include locational and physical attributes, real estate economics and it’s alignment to business strategy. This study seeks to provide an empirical contribution to the field of corporate real estate research by presenting proof on the significance of the non-financial determinants of the lease versus buy decision for corporate real estate in Johannesburg. Keywords include: Lease versus buy, Corporate real estate, Corporate strategy, Real estate, Financial modelling, Logistic regression, Kruskal-Wallis test, Likert scale.
A research report submitted to the School of Construction Economics and Management, University of Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science (Building), Johannesburg 2017
Keywords: Real property--South Africa; Real estate business--South Africa